New platform for simple and rapid protein-based affinity reactions - Kei Kubota (Nature Portfolio, 2017)
Abstract We developed a spongy-like porous polymer (spongy monolith) consisting of poly(ethylene-co-glycidyl methacrylate) with continuous macropores that allowed efficient in situ reaction between the epoxy groups and proteins of interest. Immobilization of protein A on the spongy monolith enabled high-yield collection of immunoglobulin G (IgG) from cell culture supernatant even at a high flow rate. In addition, immobilization of pepsin on the spongy monolith enabled efficient online digestion at a high flow rate.